Workforce patterns in the prevention of mother to child transmission of HIV in Côte d'Ivoire: a qualitative model - Brianne H. Rowan; Julia Robinson; Adam Granato; Claire Konan Bla; Seydou Kouyaté; Guy Vincent Djety; Kouamé Abo; Ahoua Koné; Stephen Gloyd (BMC, 2018)
Abstract Background Côte d'Ivoire continues to struggle with one of the highest rates of mother-to-child HIV transmission in West Africa, previously thought to be in part due to suboptimal workforce patterns. This study aimed to understand the process through which workforce patterns impact prevention of mother-to child transmission of HIV (PMTCT) program success, from the perspective of healthcare workers in Côte d'Ivoire. Methods A total of 142 semi-structured interviews were conducted with physicians, midwives, nurses, community counselors, social workers, pharmacists, management personnel and health aides from a nationally representative sample of 48 PMTCT sites across Côte d'Ivoire. Results Healthcare workers described three categories of workforce patterns that they perceived to be affecting PMTCT success: workforce inputs, healthcare roles and responsibilities, and facilitators of task performance. According to their descriptions, PMTCT success depends on the presence of an adequate and trained PMTCT workforce, with an interdisciplinary team of healthcare workers with flexible roles and expanded task responsibilities, and whose tasks are translated into patient care through collaboration, ongoing trainings, and appropriate motivators. Conclusions This study provides a model for understanding the impact of workforce patterns on PMTCT success in Côte d'Ivoire and provides insight into workforce-related facilitators and barriers of program performance that should be targeted in future research and interventions. It highlights the importance of workforce integration and collaboration between healthcare workers.